Practical Advice for Emergency IUD Contraception in Young Women - Norman D. Goldstuck; Dirk Wildemeersch (Hindawi Limited, 2015)
Too few women are aware of the very high efficacy of intrauterine copper devices (IUDs) to prevent pregnancy after unprotected intercourse. Women who frequently engage in unprotected intercourse or seek emergency contraception (EC) are at high risk of unplanned pregnancy and possible abortion. It is therefore important that these women receive precise and accurate information about intrauterine devices as they may benefit from using an IUD for EC as continuing contraception. Copper IUDs should be used as first choice options given their rapid onset of action and their long-term contraceptive action which require minimal thought or intervention on the part of the user. In the United States, there is only one copper IUD presently available which limits treatment options. There are numerous copper IUDs available for use in EC, however, their designs and size are not always optimal for use in nulliparous women or women with smaller or narrower uteruses. Utilization of frameless IUDs which do not require a larger transverse arm for uterine retention may have distinct advantages, particularly in young women, as they will be suitable for use in all women irrespective of uterine size. This paper provides practical information on EC use with emphasis on the use of the frameless IUD.